Local stress variation in welded joints by ICR treatment. (April 2016) - YuanZhou, Zhiyuan; Ji, Bohai; Fu, Zhongqiu; Ge, Hanbin
Abstract: Orthotropic steel decks are wildly used in long-span bridges, however fatigue cracks occurring in the decks have been reported since 1971. To improve the fatigue performance of the steel deck, some remedial techniques have been applied. Among them, is a technique called Impact Crack-Closure Retrofit treatment (ICR treatment) which has been developed in recent years. In this paper, the welded joints were treated by ICR technique, without load applied. Surface stress around the welded joints was monitored by strain gauges during the ICR process, and residual stress before and after treatment was determined by blind-hole technique respectively. The stress distribution alone the thickness direction was obtained by the micro-hardness test. Results of this study show that the residual stress after the ICR treatment can be decreased. Meanwhile compressive stress contributing to improving the fatigue strength is generated on the near-surface. The depth of the compressive stress distribution is about 5.3 mm from this test, and it well agrees with the finite element method (FEM) results. The accuracy of the FEM results also indicates that simulating the ICR treatment by an ascribed local plastic deformation is possible. Graphical abstract: Highlights: The residual stress reduction after ICR treatment is obvious and the initial stress condition of component can be improved. The distribution of compressive stress is identified through the variation of surface stress and material hardness. Propose a finite-element method for ICR treatment.